Atmospheric dispersion of argon-41 from a nuclear research reactor: measurement and modelling of plume geometry and gamma radiation field. (11th May 2004) - Lauritzen, Bent; Astrup, Poul; Drews, Martin; Jorgensen, Hans; Mikkelsen, Torben; Thykier-Nielsen, Soren; Aage, Helle; Korsbech, Uffe; Bargholz, Kim; Rojas-Palma, Carlos; Ammel, Raf
An atmospheric dispersion experiment was conducted using a visible tracer along with the routine releases of 41 Ar from the BR1 research reactor in Mol, Belgium. Simultaneous measurements of plume geometry and radiation field from 41 Ar decay were performed as well as measurements of the 41 Ar source term and the meteorological parameters. Good overall agreement is found between measurement data and model results using the mesoscale atmospheric dispersion and dose rate model RIMPUFF.